Fortalecimiento turístico del plan de desarrollo y ordenamiento territorial para la parroquia Lauro Guerrero, cantón paltas, provincia de Loja - Gallegos Tandazo, Daniela del Cisne (2022)
Tourism is considered a development strategy when it contributes to the establishment of investments in infrastructure and services in a given territory, stimulates productive diversification by generating new linkages, creates quality jobs and stimulates the local economy. For this reason, tourism planning is of vital importance to ensure a correct revitalization of tourist destinations and territorial development, based on sustainability criteria. The present research work, called "Tourism Strengthening of the Territorial Development and Planning Plan for the Lauro Guerrero parish, Canton Paltas, Province of Loja.” was designed with the objective of contributing to the positive progress of the tourist activity, where mainly the local authorities are the ones who plan and manage proposals that are for the benefit of the Parish. The general objective of this work is to strengthen the development plan and land use planning for tourism in the Lauro Guerrero parish, Canton Paltas, Province of Loja; To comply, three specific objectives were developed: 1) Carry out the diagnosis of the tourist component of the Lauro Guerrero parish, Canton Paltas, Province of Loja; which allowed through the methodology of Carla Ricaurte to determine the current situation of the Parish, its attractions and infrastructure and after that the first participatory workshop was held through a participatory methodology for its respective socialization and approval, then proceeded to prioritize tourist attractions with the matrix of prioritization of tourist attractions used in the Dry Forest Association, obtaining a total of 15 tourist attractions, the workshop also allowed to know the internal and external factors that benefit and harm the development of tourism activity. Subsequently, the information on tourist attractions was collected with the file of the Ministry of Tourism (MINTUR 2018) and it was obtained that the 15 tourist attractions are from Hierarchy II; To culminate in the development of the first objective, a survey was conducted to the PEA of Catacocha as the closest town to the Parish, to know the effective demand and obtain more information that helped to detail the strategies in the third objective. 2) Prepare a Tourism Development proposal to strengthen the Development Plan and Territorial Planning of the Lauro Guerrero Parish, through a participatory methodology, with the results obtained from the first participatory methodology workshop, a proposal was designed with each strategic objective and a second participatory workshop where each strategic objective was socialized with different aspects to consider, so that the attendees are the ones who select a proposal for each objective, to subsequently establish strategies. 3) Propose strategies to strengthen the Tourism Development proposal in the Territorial Development and Planning Plan of the Lauro Guerrero Parish, with the results obtained from the second participatory workshop, application strategies to the PDOT were designed with the general detail matrix of the strategies, of the Strategic Plan for Sustainable Tourism Development of the Cayambe 5 Canton 2017-2022, the strategies to be developed were: Implement a Tourist Information Center, Implement Online tourism promotion, Develop a Tourist Route, Propose training workshops in tourism activity and environmental care environment and Propose a plan for hiking trails and tourist signage in tourist attractions. Finally, conclusions and recommendations are described, which are mainly addressed to the Parish GAD so that it establishes agreements with public and private entities for the development of tourism projects, which will allow the parish to be known touristically and will help local people generate greater tourist awareness.